1998
DOI: 10.1034/j.1600-0501.1998.090203.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of implants in partial edentulism

Abstract: A meta-analytic technique was used to estimate the survival of implants supporting bridges or single crowns in partially edentulous patients. A survey of the literature revealed 66 studies, published between 1986 and 1996. Nine studies on single implants and 10 studies on fixed partial dentures met the inclusion criteria for the meta-analysis. Data from a total of 2686 implants, 570 single crowns (SC) and 2116 in fixed partial dentures (FPD), were analyzed. In order to calculate annual survival rates for indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(153 citation statements)
references
References 0 publications
5
142
0
6
Order By: Relevance
“…1,2 His definition of 'a direct contact between living bone and an implant, on the light microscope level' 1 describes the objective of osseointegration, but the essence of its clinical success is the reliability of long-term implant fixation, even in the presence of functional loading. This has been supported by many studies, including a metaanalysis, 3 which reported a 90% success rate for osseointegrated implants used for bridge abutments.…”
Section: History Of Implantsmentioning
confidence: 60%
“…1,2 His definition of 'a direct contact between living bone and an implant, on the light microscope level' 1 describes the objective of osseointegration, but the essence of its clinical success is the reliability of long-term implant fixation, even in the presence of functional loading. This has been supported by many studies, including a metaanalysis, 3 which reported a 90% success rate for osseointegrated implants used for bridge abutments.…”
Section: History Of Implantsmentioning
confidence: 60%
“…3,4 • Longevity on implant-supported prostheses is approx. 95% at 7 years 5 and 89% at 15 years. 6 • Conventional fixed bridgework has many variables associated with the nature of the prosthetic service, especially the health of the abutment teeth.…”
Section: Commentarymentioning
confidence: 97%
“…This number is identical to that found in a recent meta-analyis on single-tooth implants after 7±8 years of follow-up. 1 The combined curve for survival of the restorations showed a survival estimate of 833% after 4 years. It should be noted that this number is based on 240 STRs from four of the nine reports containing adequate information for a combined survival analysis.…”
Section: Commentarymentioning
confidence: 99%